Dissemination of Assistance Technology for Making Green Products Based on Waste Cooking, and Socializing the Legality of Brands - Sri Rahayu; Mieke Yustia Ayu Ratna Sari; Susi Sulastri (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
The increase in consumption of cooking oil is directly proportional to the increase in post-consumption used oil or also known as used cooking oil. This increase is not matched by an increase in public awareness of the negative impact on health and the environment. Used cooking oil can damage the environment if it is disposed of carelessly. Used cooking oil should be managed by processing it into useful products, such as recycled soap. By processing used cooking oil into recycled soap, it not only provides benefits for their own needs, but even has the opportunity to become a small and medium enterprise (UMKM). Therefore, this community service activity aims to provide training to the community, ranging from how to make used cooking oil into recycled soap, marketing strategies and legality; trademark registration, terms, fees and others. The implementation of this activity is by giving lectures on the importance of managing used cooking oil, marketing strategies, brand legality, and product manufacturing practices. The manufacture of products is guided by resource persons, followed by the community by participating in direct practice. The results of this activity are expected to increase public awareness and awareness of the negative impact of used cooking oil on health and the environment. Become a new business opportunity for the community that can be developed into MSMEs, understand marketing strategies, and the importance of making brands, and understand brand legality.